Role and place of translation practice of a specialist-ecologist at the stage of advanced higher education - Kovaleva, Tatiana (Journal of the Belarusian State University. Ecology, 2025)
The article deals with the problems associated with professionally oriented foreign language training of specialists in the sphere of ecology at the stage of advanced higher education, in particular, the significance, goals, forms of academic translation activities in the conditions of digitalization of education. Analytical work with authentic materials related to the professional activity of a specialist not only includes studying or deep-in-content reading, but also translation of original articles rich in specialized terminology and general scientific vocabulary. In the era of electronic translators and dictionaries such activity changes its forms, but does not lose its importance both in terms of development of linguistic and speech skills, and in the aspect of professional self-improvement of a specialist. Many years of experience in working with students at the stage of advanced higher education, approbation of various approaches to work with authentic literature in the master’s program allowed us to develop a certain technology of analytical reading of articles on students’ specialty for the purpose of purposeful translation and construction of a monologic statement on the basis of the translated text. The possibilities of electronic translators have accelerated the process of translation and design of secondary texts, but have not excluded the appearance of stylistic, speech terminological errors and inaccuracies. The ability to correct subtle nuances in translations related to the peculiarities of a certain scientific field becomes one of the tasks of Master’s degree programs. In addition, the secondary texts obtained with the help of electronic translation resources are the basis for creating the own monologue texts, i. e. a reverse translation should be performed: a secondary text to one’s own monologue in a foreign language using the vocabulary and grammatical constructions of the primary text. Such skills need to be purposefully developed. This article suggests ways and means of forming complex translation knowledge, skills and abilities necessary for specialists when working with professionally significant authentic materials in a foreign language, taking into account modern digital resources. The significance of the problem is due to the need to improve the quality of professionally significant linguistic training of specialists in the field of ecology, taking into account modern information technologies.